Prevalence of helicobacter pylori infection in patients with peptic ulcer disease at Kathmandu Model Hospital - Joshi, Rajesh Dhoj; Khadka, Sachin; Joshi, Deepak Man; Kadel, Arun; Dangal, Ganesh; Dongol, Yashad (Journal of Chitwan Medical College, 2018)
Introduction: Endoscopic rapid urease test is a simple and most widely used test to detect the presence of urease in the gastric mucosa. Many studies have reported prevalence of H. pylori infection in relation to age, gender and site of ulcer. Therefore, this study was designed to determine the prevalence and significance of H. pylori in peptic ulcer disease. Methods: A retrospective review was carried out for patients with peptic ulcer disease who had undergone upper GI endoscopy in Department of Internal Medicine at Kathmandu Model Hospital. The records from January 2013 to December 2017 were analyzed. Any patient with previously diagnosed peptic ulcer, history of active bleeding, cancer and incomplete records were excluded. Peptic ulcer associated with H. pylori was diagnosed on the basis of endoscopic rapid urease test. Results: Among the 418 diagnosed case of peptic ulcer disease by upper GI endoscopy from Jan 2013 to Dec 2017, 213 tested positive for H. pylori by rapid urease test. Among the positive cases, over a half were males patients. Majority (23.9%) of the patients were in the age group of 35-44 years. Prevalence of H. pylori in duodenal ulcer was 51.6% followed by combined gastro-duodenal ulcer (26.8%) and gastric ulcer (21.6%). H. pylori was significantly associated with duodenal ulcer (p